Association between religiosity or spirituality and internet addiction: A systematic review - Dossi, Francesca; Buja, Alessandra; Montecchio, Laura (Frontiers in Public Health, 2022)
Introduction The literature provides evidence of religiosity being associated with physical and mental health, and also with behavioral addictions. This systematic review examines the data on the link between religiosity or spirituality and the emerging internet addictions. Methods A systematic literature review was conducted in the PubMed and Scopus databases to identify observational (cross-sectional, cohort, and case-control) studies conducted on adolescents and young adults to investigate the association between religiosity or spirituality and internet addiction. Of the 854 articles identified in the databases, 13 met our inclusion criteria and were included in our systematic review. Results Eleven of the 13 studies reviewed specifically investigated religiosity and internet addiction: six found an inverse association between religiosity and internet addiction; three found no evidence of any association; and one found a direct association. One study examining both religiosity and spirituality generated mixed results. Only one study investigated spirituality unrelated to religion, and found a direct association with internet addiction. Two of three studies specifically considering internet gaming addiction found it inversely associated with high levels of religiosity, while the third found no association. Conclusion This review supports a possible role for religiosity as a protective factor, as emerged from the majority of the studies examined. Religiosity also seemed to be associated with lower internet gaming rates among adolescents.